A Companion to Geoffrey of Monmouth - Byron-Smih, Joshua (Brill, 2020)
A Companion to Geoffrey of Monmouth brings together scholars from a range of disciplines to provide an updated scholarly introduction to all aspects of his work. Arguably the most influential secular writer of medieval Britain, Geoffrey (d. 1154) popularized Arthurian literature and left an indelible mark on European romance, history, and genealogy. Despite this outsized influence, Geoffrey's own life, background, and motivations are little understood. The volume situates his life and works within their immediate historical context, and frames them within current critical discussion across the humanities. By necessity, this volume concentrates primarily on Geoffrey's own life and times, with the reception of his works covered by a series of short encyclopaedic overviews, organized by language, that serve as guides to further reading.